The Role of Parents in Children's Achievement in Cimahi United Football School - Rifqi fajar Andriawan; Budiman; Agus Santosa (Journal of Physical and Outdoor Education, 2025)
The Role of Parents in Children's Achievement in Cimahi United Football School. The purpose of this study was to determine how big the role of parents is in supporting children's achievements in Cimahi United football school. This study is a type of quantitative description research using a survey method, from the results of the study obtained, the researcher took all 18 parents as samples, the researcher used a questionnaire with a total of 35 questions that had been tested for validity and rehabilitation. The data collection technique used was by distributing questionnaires directly using sheets of paper to 18 respondents. After the data was collected, the data was analyzed using a percentage formula with the results of the study of the role of parents towards children's achievements at the Cimahi United soccer school "Very Good" of (0%), the category "Good" of 16.67%, the category "Enough" of 33.33%, the category "Less" of 44.44%, the category "Very Less" 5.56%. The results can be concluded that the Role of Parents towards Children's Achievements at the Cimahi United Soccer School is Less, this shows that there are still many parents who have not maximally carried out their role in supporting children's training activities and achievements at the Cimahi United soccer school. The intended parental support includes aspects of attention, nutrition, provision of facilities and infrastructure and a supportive environment.